In Fungal Intracellular Pathogenesis, Form Determines Fate - Robin C. May (American Society for Microbiology, 2018)
ABSTRACT For pathogenic microbes to survive ingestion by macrophages, they must subvert powerful microbicidal mechanisms within the phagolysosome. After ingestion, Candida albicans undergoes a morphological transition producing hyphae, while the surrounding phagosome exhibits a loss of phagosomal acidity. However, how these two events are related has remained enigmatic. Now Westman et al. (mBio 9:e01226-18, 2018, https://doi.org/10.1128/mBio.01226-18) report that phagosomal neutralization results from disruption of phagosomal membrane integrity by the enlarging hyphae, directly implicating the morphological transition in physical damage that promotes intracellular survival. The C. albicans intracellular strategy shows parallels with another fungal pathogen, Cryptococcus neoformans, where a morphological changed involving capsular enlargement intracellularly is associated with loss of membrane integrity and death of the host cell. These similarities among distantly related pathogenic fungi suggest that morphological transitions that are common in fungi directly affect the outcome of the fungal cell-macrophage interaction. For this class of organisms, form determines fate in the intracellular environment.